Micro-flow synthesis and structural analysis of sterically crowded diimine ligands with five aryl rings - Fuse, Shinichiro; Tanabe, Nobutake; Tannna, Akio; Konishi, Yohei; Takahashi, Takashi (Beilstein Journal of Organic Chemistry, 2013)
Sterically crowded diimine ligands with five aryl rings were prepared in one step in good yields using a micro-flow technique. X-ray crystallographic analysis revealed the detailed structure of the bulky ligands. The nickel complexes prepared from the ligands exerted high polymerization activity in the ethylene homopolymerization and copolymerization of ethylene with polar monomers.
Keywords: amidine formation; diimine; flow chemistry; polymerization